The South Asia papers : a critical anthology of writings - Cohen, Stephen P., 1936- (Brookings Institution Press, 2016)
"Stephen Philip Cohen, the scholar who virtually created the field of South Asian security studies, has curated a unique collection of the most interesting and important articles, chapters, and speeches from his fifty-year career. Cohen, often described as the "dean" of U.S. South Asian studies, is a dominant figure in the fields of military history, military sociology, and South Asia's strategic emergence. This exceptional collection includes material that have never appeared in book form, including Cohen's original essays on the region's military history, the transition from British rule to independence, the role of the armed forces in India and Pakistan, the pathologies of India-Pakistan relations, South Asia's growing nuclear arsenal, and America's fitful (and forgetful) regional policy. These original writings show how Cohen developed a still-relevant theory of regional conflict, and how his views evolved over the years-tracking the development of South Asian security studies"--